2013
DOI: 10.1007/978-1-4614-8289-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45 in Stress Signaling, Cell Cycle Control, and Apoptosis

Abstract: The first identified Gadd45 gene, Gadd45a, encodes a ubiquitously expressed protein that is often induced by DNA damage and other stress signals associated with growth arrest and apoptosis. This protein and the other two members of this small gene family, Gadd45b and Gadd45g, have been implicated in a variety of the responses to cell injury including cell cycle checkpoints, apoptosis, and DNA repair. In vivo, many of the prominent roles for the Gadd45 proteins are associated with signaling mediated by p38 mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
255
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(267 citation statements)
references
References 82 publications
11
255
1
Order By: Relevance
“…GADD45A and CDKN1A (p21), both of which regulate cell cycle arrest 28,29 and are induced by p53, were significantly upregulated in v2-depleted cells compared with controls in a p53+, but not p53i, background (Figure 4d and Supplementary Figure S3B), suggesting they may contribute to the p53-dependent S-phase arrest in v2-depleted cells. On the other hand, proliferating cell nuclear antigen (PCNA), which is required for progression of DNA replication, 30 was significantly reduced in TP8i cells in both the p53+ and p53i settings ( Figure 5e).…”
Section: Resultsmentioning
confidence: 99%
“…GADD45A and CDKN1A (p21), both of which regulate cell cycle arrest 28,29 and are induced by p53, were significantly upregulated in v2-depleted cells compared with controls in a p53+, but not p53i, background (Figure 4d and Supplementary Figure S3B), suggesting they may contribute to the p53-dependent S-phase arrest in v2-depleted cells. On the other hand, proliferating cell nuclear antigen (PCNA), which is required for progression of DNA replication, 30 was significantly reduced in TP8i cells in both the p53+ and p53i settings ( Figure 5e).…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggests that modulation of translation efficiency might reinforce the activation of p53-dependent apoptosis, a process that could be important given the generally weaker transcriptional control of p53 target genes in the apoptosis group. 24 We validated by qPCR TRIAP1, 25 TRAF4 26 and GADD45G 27 (the full list of genes is presented in Supplementary Figure S3A). According to ChIP-seq data on MCF7 cells, these genes are direct p53 targets.…”
Section: Resultsmentioning
confidence: 99%
“…Increased expression of H2AFX and BRCA-1 in the PhIP-treated group as well as data from comet assays, ROS monitoring and immunofluorescence with anti-DNA adduct antibodies support this idea [7]. Previous studies have shown that BRCA-1, P-53 and other tumor suppressor genes are able to increase GADD-45 expression [16][17][18]. Catalase and GADD-45 are associated with the FOXO pathway; however, these two genes perform different functions of detoxification and DNA repair, respectively.…”
Section: Brief Reportmentioning
confidence: 77%